Translation suppression promotes stress granule formation and cell survival in response to cold shock - Hofmann, Sarah; Khaimov, Valeria; Bankhead, Peter; Bukau, Bernd; Stoecklin, Georg (Molecular biology of the cell, 2012)
Cells respond to different types of stress by inhibition of protein synthesis and subsequent assembly of stress granules (SGs), cytoplasmic aggregates that contain stalled translation preinitiation complexes. Global translation is regulated through the translation initiation factor eukaryotic initiation factor 2α (eIF2α) and the mTOR pathway. Here we identify cold shock as a novel trigger of SG assembly in yeast and mammals. Whereas cold shock-induced SGs take hours to form, they dissolve within minutes when cells are returned to optimal growth temperatures. Cold shock causes eIF2α phosphorylation through the kinase PERK in mammalian cells, yet this pathway is not alone responsible for translation arrest and SG formation. In addition, cold shock leads to reduced mitochondrial function, energy depletion, concomitant activation of AMP-activated protein kinase (AMPK), and inhibition of mTOR signaling. Compound C, a pharmacological inhibitor of AMPK, prevents the formation of SGs and strongly reduces cellular survival in a translation-dependent manner. Our results demonstrate that cells actively suppress protein synthesis by parallel pathways, which induce SG formation and ensure cellular survival during hypothermia.
Gesehen am 16.08.2018